2021
DOI: 10.3390/atmos12070806
|View full text |Cite
|
Sign up to set email alerts
|

Air Pollution Observations in Selected Locations in Poland during the Lockdown Related to COVID-19

Abstract: The coronavirus disease (COVID-19) has caused huge changes in people’s daily habits and had a significant impact on the economy. The lockdowns significantly reduced road traffic and meant that many people worked remotely. Therefore, the question arose as to how the reduced road traffic and stays of residents at home affected the degree of pollution and the structure of major air pollutants. To answer this question, the article presents an analysis of changes in typical air pollutants (PM10, PM2.5, NO2) in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 43 publications
1
11
0
Order By: Relevance
“…In this study we demonstrated that in general, up to the second lockdown (November 2020 -January 2021), the pandemic significantly reduced NO x levels in large Polish cities by 6% to 21% in daily mean and by 3% to 19% in daily maximum concentrations compared to the pre-pandemic period. Similar decrease of NO 2 pollution on urban air quality stations in Poland during first lockdown (April 2020) (~20%) was observed by Grzybowski (2021), while slightly weaker effect (6-11%) was found for this period by Rogulski and Badyda (2021), which, in comparison to other European cities, represents a relatively low reduction (Solberg et al, 2021). More significant drops in NO x concentration were recorded at traffic monitoring stations than at background stations, which has been also confirmed by the results from UK (Jephcote et al, 2021;Ropkins & Tate, 2021) and may be associated with a significant decrease in car traffic in Polish cities in the first stages of the pandemic (Warsaw Municipal Roads Management, 2021).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…In this study we demonstrated that in general, up to the second lockdown (November 2020 -January 2021), the pandemic significantly reduced NO x levels in large Polish cities by 6% to 21% in daily mean and by 3% to 19% in daily maximum concentrations compared to the pre-pandemic period. Similar decrease of NO 2 pollution on urban air quality stations in Poland during first lockdown (April 2020) (~20%) was observed by Grzybowski (2021), while slightly weaker effect (6-11%) was found for this period by Rogulski and Badyda (2021), which, in comparison to other European cities, represents a relatively low reduction (Solberg et al, 2021). More significant drops in NO x concentration were recorded at traffic monitoring stations than at background stations, which has been also confirmed by the results from UK (Jephcote et al, 2021;Ropkins & Tate, 2021) and may be associated with a significant decrease in car traffic in Polish cities in the first stages of the pandemic (Warsaw Municipal Roads Management, 2021).…”
Section: Discussionsupporting
confidence: 79%
“…In some cases, decreased concentrations of pollutants during lockdowns have been overwhelmed by unfavourable weather conditions that still caused severe air pollution events, even while the traffic was significantly reduced (Wang et al, 2020) Few papers show the impact of COVID-19 mobility restrictions on air quality in Poland. They focus on the first lockdown only and use either satellite data (Filonchyk et al, 2021a(Filonchyk et al, , 2021bGrzybowski et al, 2021) or ground data from air quality monitoring stations (Rogulski & Badyda, 2021) and mobile measurements (Polednik, 2021) to investigate changes in air pollutants concentration during one particular period of time. Therefore, it is crucial to check what changes in air quality have occurred as the COVID-19 pandemic unfolded and verify whether introduced administrative regulations had the same impact on air pollution during three subsequent lockdowns in Poland.…”
Section: Introductionmentioning
confidence: 99%
“…This results in elevated emissions of PM and PM-bound polycyclic hydrocarbons, especially between late autumn and early spring ( Anioł et al, 2021 , Nazar and Niedoszytko, 2022 ). Moreover, contrary to many world regions, the COVID-19 lockdown in Poland was not associated with a temporary decline in PM emissions, while in selected locations, they were even increased ( Rogulski and Badyda, 2021 ).…”
Section: Introductionmentioning
confidence: 90%
“…This is particularly relevant for regions such as Central Europe, where wood and coal combustion still plays a significant role in domestic heating and increases the emissions of PM and PM-bound polycyclic aromatic hydrocarbons such as B(a)P between late autumn and early spring ( Anioł et al, 2021 ; Nazar and Niedoszytko, 2022 ). Although lockdowns associated with the COVID-19 pandemic have resulted in temporary declines in the emission of air pollutants in different world regions ( Venter et al, 2020 ; Xu et al, 2020 ), the research shows that in countries such as Poland, the pollution with PM did not decrease or even significantly increased in the selected location ( Rogulski and Badyda, 2021 ).…”
Section: Introductionmentioning
confidence: 91%